Attachment, Emotion Regulation, Childhood Abuse and Assault: Examining Predictors of NSSI Among Adolescents. Issue 4 (2nd October 2017) - Tatnell, Ruth; Hasking, Penelope; Newman, Louise; Taffe, John; Martin, Graham
Abstract : In this study we examined the relative risk of Non-Suicidal Self-Injury (NSSI) associated with a history of physical and sexual abuse/assault, poor attachment relationships, and poor emotion regulation among adolescents. A total of 2, 637 adolescents (aged 12–15 years) completed questionnaires at 3 time-points: baseline, 12, and 24 months later. Across the study, 9.4% reported a history of NSSI. Each of past or recent abuse/assault, poor attachment relationships, and poor emotion regulation was associated with NSSI. We also observed a potential "high-risk" group among those reporting recent sexual abuse or assault. Knowledge of abuse history, recent sexual assault, attachment, and emotion regulatory ability will enable clinicians to assist adolescents in avoiding some of the more negative outcomes of these, including NSSI.